Python Reinforcement Learning : Solve complex real-world problems by mastering reinforcement learning algorithms using OpenAI Gym and TensorFlow /: Solve complex real-world problems by mastering reinforcement learning algorithms using OpenAI Gym and TensorFlow. (2019) - Ravichandiran, Sudharsan; Saito, Sean; Shanmugamani, Rajalingappaa; Wenzhuo, Yang
No abstract available